Application of whole‐lesion histogram analysis of pharmacokinetic parameters in dynamic contrast‐enhanced MRI of breast lesions with the CAIPIRINHA‐Dixon‐TWIST‐VIBE technique. Issue 1 (3rd June 2017) - Li, Zhiwei; Ai, Tao; Hu, Yiqi; Yan, Xu; Nickel, Marcel Dominik; Xu, Xiao; Xia, Liming
Abstract : Purpose: To investigate the application of whole‐lesion histogram analysis of pharmacokinetic parameters for differentiating malignant from benign breast lesions on dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI). Materials and Methods: In all, 92 women with 97 breast lesions (26 benign and 71 malignant lesions) were enrolled in this study. Patients underwent dynamic breast MRI at 3T using a prototypical CAIPIRINHA‐Dixon‐TWIST‐VIBE (CDT‐VIBE) sequence and a subsequent surgery or biopsy. Inflow rate of the agent between plasma and interstitium ( K trans ), outflow rate of agent between interstitium and plasma ( K ep ), extravascular space volume per unit volume of tissue ( v e ) including mean value, 25th/50th/75th/90th percentiles, skewness, and kurtosis were then calculated based on the whole lesion. A single‐sample Kolmogorov–Smirnov test, paired t ‐test, and receiver operating characteristic curve (ROC) analysis were used for statistical analysis. Results: Malignant breast lesions had significantly higher K trans, K ep, and lower v e in mean values, 25th/50th/75th/90th percentiles, and significantly higher skewness of v e than benign breast lesions (all P < 0.05). There was no significant difference in kurtosis values between malignant and benign breast lesions (all P > 0.05). The 90th percentile of K trans, the 90th percentile of K ep, and the 50th percentile of v e showed the greatest areas under the ROC curve (AUC) for each pharmacokinetic parameter derived from DCE‐MRI. The 90th percentile of K ep achieved the highest AUC value (0.927) among all histogram‐derived values. Conclusion: The whole‐lesion histogram analysis of pharmacokinetic parameters can improve the diagnostic accuracy of breast DCE‐MRI with the CDT‐VIBE technique. The 90th percentile of K ep may be the best indicator in differentiation between malignant and benign breast lesions. Level of Evidence: 4 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2018;47:91–96.